Ethnic Questions in the Hungarian Migration Policy until 1914 – Forming the Main Lines of a State-Backed Action Concerning the Migrants in the United - Balázs Pálvölgyi (Journal on European History of Law, 2011)
In the second half of the 19th century, when the mass-migration flow started from Hungary mainly to the United States and to other American destinations, the Hungarian government slowly revealed the complexity of this social phenomenon. In the early years of the Hungarian migration, it was the economic and military question, which gave a push to the governmental steps in a higher level, and from the end of the 19th century, it was the ethnic problem, which made the Hungarian policy ambiguous.